Digital Place Narratives and Content Analysis in Tourism Research - Punziano, Gabriella (Italian Sociological Review, 2022)
The aim of this article is to introduce content analysis in the field of social research on tourism. Among other techniques, content analysis has undergone a revitalisation and acceleration in recent years, especially following a process of digitalisation and the spread of blogs, websites, social media, online reviews and digital spaces in which it is possible to comment, release content and express one’s own opinion, making the information available directly on the web increasingly numerous. On the basis of these premises, the aim of this article is to provide the reader with a definition of the technique by tracing, some specificities and useful characteristics. Subsequently, it will outline the difference between the quantitative and qualitative approaches to content analysis by examining the digital scenario and its particularities, especially the kind of digital data of which it makes use. Finally, it will offer a practical example of its application to the analysis of tourism narratives in digital spaces, centred on Quartieri Spagnoli in Naples. The example will be used in order to show how this technique could be a solution for specific cognitive objectives that are increasingly fitting in the production of tourism studies which adopt digital data in even more articulated designs that may involve a combination of different techniques.